2015
DOI: 10.1111/pme.12750
|View full text |Cite
|
Sign up to set email alerts
|

Basal Pain Sensitivity does not Predict the Outcome of Multidisciplinary Chronic Pain Treatment

Abstract: Results show that basal pain sensitivity is not a reliable predictor of treatment outcome in mixed diagnosis multidisciplinary pain management programs, possibly due to the heterogeneity of patients enrolled in such programs. Clinically useful predictors of treatment success in this setting remain to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
(41 reference statements)
4
18
0
Order By: Relevance
“…The reduction of depressive symptoms at the end of the treatment ( d =0.53) was comparable to some previous studies (e.g., Pieh et al [ 24 ]: d =0.54; Hampel et al [ 21 ]: d =0.57; Ruscheweyh et al [ 26 ]: d =0.42) but smaller than that observed by Borys et al [ 17 ] ( d =0.77), Moradi et al [ 22 ] ( d =0.7), and Pöhlmann et al [ 25 ] ( d =0.80). In contrast to Borys et al [ 17 ], Hampel et al [ 21 ], and Ruscheweyh et al [ 26 ] who reported that depression rates at follow-up (twelve months and six months, resp.) were no longer different from pretreatment, the reduction in symptoms of depression was significant at twelve-month follow-up in the current study ( d =0.38).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The reduction of depressive symptoms at the end of the treatment ( d =0.53) was comparable to some previous studies (e.g., Pieh et al [ 24 ]: d =0.54; Hampel et al [ 21 ]: d =0.57; Ruscheweyh et al [ 26 ]: d =0.42) but smaller than that observed by Borys et al [ 17 ] ( d =0.77), Moradi et al [ 22 ] ( d =0.7), and Pöhlmann et al [ 25 ] ( d =0.80). In contrast to Borys et al [ 17 ], Hampel et al [ 21 ], and Ruscheweyh et al [ 26 ] who reported that depression rates at follow-up (twelve months and six months, resp.) were no longer different from pretreatment, the reduction in symptoms of depression was significant at twelve-month follow-up in the current study ( d =0.38).…”
Section: Discussionsupporting
confidence: 89%
“…The patients' pain intensity improved from pre- to posttreatment with a medium effect size of d =0.59. This is comparable to the medium effect sizes of d =0.64 found by Hampel et al [ 21 ], d =0.6 reported by Moradi et al [ 22 ], and d =0.51 found by Ruscheweyh et al [ 26 ]. However, Pieh et al [ 24 ] and Pöhlmann et al [ 25 ] reported larger effect sizes of d =1.0 and d =0.69 − 0.98, respectively, concerning the reduction of the pain intensity at the end of a 5-week multimodal day-clinic treatment for patients with chronic pain.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations